2020
DOI: 10.1101/2020.03.04.977603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular mechanism of regulation of the purine salvage enzyme XPRT by the alarmones pppGpp, ppGpp, and pGpp

Abstract: 1The alarmones pppGpp and ppGpp mediate starvation response and maintain purine homeostasis 2 to protect bacterial species. Xanthine phosphoribosyltransferase (XPRT) is a purine salvage 3 enzyme that produces the nucleotide XMP from PRPP and xanthine. Combining structural, 4 biochemical and genetic analyses, we show that pppGpp and ppGpp, as well as a third putative 5 alarmone pGpp, all directly interact with XPRT and inhibit XPRT activity by competing with its 6 substrate PRPP. Structural analysis reveals tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…These results confirmed strong pGpp binding to guanosine nucleotide synthesis proteins (Hpt1, Gmk, and Xpt). Enzyme kinetic assay of Xpt 32 and HprT (Fig. 3e ) confirmed that pGpp inhibited their activities more potently than ppGpp and pppGpp.…”
Section: Resultsmentioning
confidence: 70%
“…These results confirmed strong pGpp binding to guanosine nucleotide synthesis proteins (Hpt1, Gmk, and Xpt). Enzyme kinetic assay of Xpt 32 and HprT (Fig. 3e ) confirmed that pGpp inhibited their activities more potently than ppGpp and pppGpp.…”
Section: Resultsmentioning
confidence: 70%
“…Both HprT and XprT use PRPP as a phosphoribose donor to convert the purine bases hypoxanthine and guanine to IMP and GMP (HprT) or xanthine to XMP (XprT) (FIG. 2a) 4,64,88,96 . XprT is most potently inhibited by pGpp and ppGpp, which bind at the PRPP binding site (FIG.…”
Section: Nucleotide Synthesismentioning
confidence: 99%
“…XprT is most potently inhibited by pGpp and ppGpp, which bind at the PRPP binding site (FIG. 2b) and protect cells from excess environmental xanthine 96 . The (pp)pGpp-bound form of HprT exists as an apo-tetramer (FIG.…”
Section: Nucleotide Synthesismentioning
confidence: 99%
“…There are six crystal structures of (p)ppGpp and nucleotide metabolic enzymes complexes available in the Protein Data Bank which includes Xanthine phosphoribosyltransferase (XPRT) ( Anderson et al, 2020 ), Pyrimidine/purine nucleotide 5′-monophosphate nucleosidase (nucleosidase, PpnN) ( Zhang et al, 2019 ), Hypoxanthine phosphoribosyltransferase (HPRT) ( Anderson et al, 2019 ), Amidophosphoribosyltransferase (PurF) ( Wang et al, 2019 ), Guanylate kinase ( Liu et al, 2015 ; Table 1 ). A most striking feature of the structures of these enzyme-(p)ppGpp complexes are oligomeric stoichiometry in these complexes.…”
Section: Resultsmentioning
confidence: 99%